Evaluation of echocardiography monitoring in myotonic dystrophy type 1 patients - Bovenkerk, D. S. H.; Janssen, C. E. W.; Van den Heuvel, F. M. A.; Joosten, I. B. T.; Den Uijl, D.; Van Engelen, B. G. M.; Van Kuijk, S. M. J.; Nijveldt, R.; Evertz, R.; Faber, C. G.; Vernooy, K.; Bijvoet, G. P. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionMyotonic Dystrophy type 1 (DM1) is the most prevalent genetic neuromuscular disorder. The potential cardiac involvement, including arrhythmia and left ventricular dysfunction, demands routine follow-up with ECG and echocardiography, however recommendations on the interval of echocardiographic follow-up varies substantially. The aim of this study is to evaluate the long-term prevalence of LV dysfunction during echocardiographic follow-up of patients with DM1. Secondly, we aim to assess the association between structural abnormalities on echocardiography, ECG and clinical parameters.MethodsThis retrospective cohort study with DM1 patients was conducted in Maastricht University Medical Center (MUMC+) and Radboud University Medical Center. All patients above 18 years old were included through the Dutch DM1 patient registry (MYODRAFT study). Patients were evaluated between January 2010 and December 2023. A total of 273 patients were included, in whom echocardiographic data was collected and correlated with clinical data, neuromuscular status and ECG parameters.ResultsAt baseline 20/273 (7.3%) patients had LV dysfunction (LVEF < 50% and/or LV dilatation). When newly detected LVEF <50% alone is considered then the yield of routine echocardiography follow-up was: 9/273 at baseline (3%), 2/84 at 36 months (2%), 9/184 at 72 months (5%) and 10/117 at the interval beyond 72 months (8%). The only clear correlation between ECG and echocardiography abnormalities was a widened QRS interval 125 ± 31 ms vs. 103 ± 19 ms (p = 0.007). This was also demonstrated in the multivariable analysis. Of the DM1 patients developing LV dysfunction, the median interval between the diagnosis of DM1 and the first echocardiogram detecting LV dysfunction was 181 months (15.1 years) with an interquartile range of 85–301 months (7.0–25.1 years).DiscussionBased on the data of this large retrospective study, the occurrence of LV dysfunction in DM1 patients is rather low (7.4%) at baseline and increases with 6.5% at 72 months follow-up. There is a significant correlation between LV dysfunction and a widened QRS interval. Which could prompt earlier echocardiographic follow up in this patient group. Routine echocardiography is useful in DM1 however the interval of echocardiography could be shifted more towards 5 years in asymptomatic patients because of the slow progressive nature of the disease.